Fluorescence cholangiography during laparoscopic cholecystectomy in a patient with situs inversus totalis: a case report and literature review - Narongsak Rungsakulkij; Pongsatorn Tangtawee (BMC Surgery, 2017)
Abstract Background Situs inversus totalis is a rare autosomal disorder in which the patient’s affected visceral organs are a perfect mirror image of their normal positions. Surgery in these patients is technically challenging. Minimally invasive surgery such as laparoscopic cholecystectomy is the standard treatment for symptomatic cholelithiasis, but it can be difficult to perform. Laparoscopic cholecystectomy in patients with situs inversus totalis may be even more technically challenging. Fluorescence cholangiography is a new innovation in the field of navigation surgery. This procedure is safe and easy to perform, its findings are easy to interpret, and it does not require a learning curve or radiographs. It can be used in real time during surgery to identify extrahepatic biliary structures. Case presentation We herein report a case of situs inversus totalis in a Thai patient with a history of biliary pancreatitis. He underwent laparoscopic cholecystectomy with intraoperative fluorescence cholangiography. The operation was successfully completed without complications. To the best of our knowledge, this is the first case report of the use of fluorescence cholangiography during laparoscopic cholecystectomy in a patient with situs inversus. Conclusion Fluorescence cholangiographyis a new navigational surgical technique with which to identify extrahepatic biliary structures. It can be used as an adjunct technique during laparoscopic cholecystectomy to avoid biliary tract injury in difficult cases.